Early science learning: The effects of teacher talk. (February 2021) - Studhalter, Ueli T.; Leuchter, Miriam; Tettenborn, Annette; Elmer, Anneliese; Edelsbrunner, Peter A.; Saalbach, Henrik
Abstract: Our study addresses the relationship between teacher talk and children's conceptual learning in early science instruction. We examined the role of teacher talk in N = 32 kindergarten classes. The teachers were video-recorded at the beginning of a four-week instruction phase while assisting a group of children who were dealing with a learning unit on floating and sinking. The coding of teacher talk included expressions that were pertinent to the content (content-specific vocabulary) and talk that performed an underlying scaffolding function (scaffolding utterances). Teachers' scaffolding utterances were assigned to four sub-types. The children's conceptual understanding was measured in individual sessions in a pre-post design. The results of two different analytic approaches indicated that the teachers' content-specific language acted as a positive predictor of the children's learning outcomes whereas both positive and negative effects were found with respect to the sub-types of scaffolding utterances. Highlights: Teacher talk in early science instruction was analyzed on the basis of video recordings. Teachers' use of content-specific vocabulary predicts children's learning outcomes. Teacher talk that is intended to activate prior knowledge predicts children's learning. The analysis of teacher talk in terms of scaffolding functions showed both positive and negative effects.